Seismic hazards in Southern California : probable earthquakes, 1994 to 2024 - Working group on California earthquake probabilities. (2013)
We combine geodetic, geologic, and seismic information to estimate frequencies of damaging earthquakes in three types of seismotectonic zone. Type A zones contain faults for which paleoseismic data suffice to estimate conditional probabilities. Type B zones contain faults with insufficient data for conditional probability analysis. Type C zones contain diverse or hidden faults. Each zone is assumed to have randomly distributed earthquakes plus characteristic earthquakes on specific faults. Our “cascade” model allows for multiple-segment earthquakes. Within each zone, distributed earthquakes are assumed uniform in time and space, with a truncated Gutenberg-Richter magnitude distribution. Thus, seismic hazard is defined by the characteristic earthquake rate, the rate of all distributed events, and the limiting (characteristic) magnitude. Limiting magnitudes are determined from fault lengths, while earthquake rates are determined by observed seismicity and seismic moment rate.